Community directives (effects) - Martínez Caballero, Juan (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
One of the major problems to be confronted by the Court of Justice of the European Union is the failure of Member States to comply with the obligation to transpose a Directive into national law. Since the judgment of the Court of 17 December 1970, case SACE (C-33/70), the Court has provided some legal effects to directives in order to enforce them. Likewise, the aforementioned Court has also enabled individuals to bring proceedings against a Member State, which has either still not transposed the Directive or has failed to transpose it correctly, with the aim of achieving the effectiveness of the Directive. That is to say, the application seeks to avoid this effectiveness to be hindered by any non-transposition into national law.